Does touch inhibit visual imagery? A case study on acquired blindness. Issue 2 (19th April 2017) - von Trott zu Solz, Jana; Paolini, Marco; Silveira, Sarita
Abstract : In a single‐case study of acquired blindness, differential brain activation patterns for visual imagery of familiar objects with and without tactile exploration as well as of tactilely explored unfamiliar objects were observed. Results provide new insight into retrieval of visual images from episodic memory and point toward a potential tactile inhibition of visual imagery.